Finishing / Muhamad Rashid Ab Aziz - Ab Aziz, Muhamad Rashid (2007)
Nowaday, our country is on the verge of technology advances and country advancement, construction industry has been given a priority from our goverment. The reason behind this hard work is to provide enough work force and variety of economy trends to the nation.